If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 1 = -31 Reorder the terms: 1 + -4x = -31 Solving 1 + -4x = -31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = -31 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -31 + -1 -4x = -31 + -1 Combine like terms: -31 + -1 = -32 -4x = -32 Divide each side by '-4'. x = 8 Simplifying x = 8
| 2x-3(-3.6)=13 | | y=x^2+13x+12 | | 5x-7y=-35 | | y/.25+12=77 | | -7/4a=21 | | -(19y+22)-18+(-19y-21)+7y=22 | | (b/2.8)+83=39 | | 1.5(x+1)-4=-2-7 | | 6x-4-5x=10+8 | | 12-25-13=0 | | -3y=11 | | 42/7 | | 3x^2-8i=12-(12y)i | | 5x-17-2x=6x-1-x-8 | | 1/5x+3=2x-24 | | -8r+3=-64 | | 9+12=-9-3z | | 25-3x=-7x+4 | | 7-3y+2=0 | | 9x-5(x+6)=-10 | | (r/1.2)+7.5=45 | | 21k-17+8k=4-21k-6 | | 2+6+7rs= | | 31.9/5.8 | | y=-6x+24 | | 1/2=q+2/3 | | Y=3/5x^2+30+382 | | -7+4x=-3 | | n-(-8)=-2 | | 6[y]=-12 | | 5x-2+3x=2x+6-4 | | -[6x+(8x+5)]=8-(7x+9) |